LITERATURE REVIEW: STUDENTS' CREATIVE THINKING SKILLS THROUGH DISCOVERY LEARNING MODEL - Mu’izzah, Nailil; Waluya , Budi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Many studies have focused on using the Discovery Learning model to improve students' creative thinking skills. To support researchers and educators in the field of mathematics education, it is imperative to identify these studies, assess their progress, and summarize in general to provide appropriate advice. This study aims to determine the effect of the Discovery Learning model on students' mathematical creative thinking skills from 2018-2024. This study analyzed 23 journal articles obtained through Google Scholar. The research method used is Systematic Literature Review (SLR). The results of this SLR show that most of the studies examining students' creative thinking skills through Discovery Learning were conducted in 2023, mainly focusing on SMP/MTS. The most widely used method is quantitative. This study can be concluded that 1) the Discovery Learning learning model significantly improves students' creative thinking skills on fluency, flexibility, originality, and elaboration indicators with a moderate to high level of improvement, 2) this model can be used for various levels of education and mathematics topics, and can be combined with other methods such as HOTS questions, e-modules, and Geogebra to improve learning outcomes.